Gaining Surgical Access for Repositioning the Inferior Alveolar Neurovascular Bundle - Saif Yousif Abdullah Al-Siweedi; P. Nambiar; P. Shanmuhasuntharam; W. C. Ngeow (The Scientific World Journal)
This study is aimed at determining anatomical landmarks that can be used to gain access to the inferior alveolar neurovascular (IAN) bundle. Scanned CBCT (i-CAT machine) data of sixty patients and reconstructions performed using the SimPlant dental implant software were reviewed. Outcome variables were the linear distances of the mandibular canal to the inferior border and the buccal cortex of the mandible, measured immediately at the mental foramen (D1) and at 10, 20, 30, and 40 mm (D2–D5) distal to it. Predictor variables were age, ethnicity, and gender of subjects. Apicobasal assessment of the canal reveals that it is curving downward towards the inferior mandibular border until 20 mm (D3) distal to the mental foramen where it then curves upwards, making an elliptic-arc curve. The mandibular canal also forms a buccolingually oriented elliptic arc in relation to the buccal cortex. Variations due to age, ethnicity, and gender were evident and this study provides an accurate anatomic zone for gaining surgical access to the IAN bundle. The findings indicate that the buccal cortex-IAN distance was greatest at D3. Therefore, sites between D2 and D5 can be used as favorable landmarks to access the IAN bundle with the least complications to the patient.